Persepsi Terhadap Aplikasi Pengelolaan Keuangan Studi Kasus Pengelola BUMDes di Kawasan Ekonomi Khusus Mandalika - Hikmah Julia; Embun Suryani; Diswandi Diswandi (Universitas Mataram, 2022)
The purpose of this study was to determine the perceptions of BUMDes managers regarding financial management applications as well as the benefits and feasibility of the application to be used as a BUMDes accounting information system. This research was analyzed descriptively using the phenomenological method. Data analysis used interactive analysis techniques, which included data collection, data reduction, data presentation, and conclusion. The results of this study indicate that the perception of BUMDes managers using financial management applications is dominant to positive perceptions. The results of interviews with BUMDes managers prove that financial management applications can increase BUMDes business productivity, improve performance, work faster and easier, store data safer, and give the resulting accounting information clearer. Most BUMDes managers give some positive perception. However, some BUMDes managers still choose to keep using manual records because the financial management application is considered not to follow the business units' run. From the results of data analysis, financial management applications are appropriate for use as BUMDes financial records that have met accounting standards and are better.